Multidimensional Design of Anisotropic Polymer Particles from Solvent-Evaporative Emulsion - Ku, Kang Hee; Shin, Jae Man; Yun, Hongseok; Yi, Gi-Ra; Jang, Se Gyu; Kim, Bumjoon J. (WILEY-V C H VERLAG GMBH, 2018)
Colloidal particles with controlled shape and internal structure have attracted great attention due to their novel morphologies and various potential applications. Among the diverse synthetic strategies toward anisotropically shaped polymer particles, facile and accurate engineering of such structures remains challenging. This review highlights the synthetic approaches to manipulate the shape of polymer particles driven by phase separation in emulsions upon solvent evaporation. And, special attention is given to the thermodynamic and kinetic principles of particle shape control, followed by detailed experimental examples and their applications. Major synthetic strategies for the preparation of nonspherical block copolymer (BCP) particles by evaporation of solvent from BCP-containing emulsions are discussed as follows: engineering of i) interfacial properties of the confining emulsion droplets, ii) particle (or droplet) size, iii) segregation behavior of BCPs within the droplet, and iv) solvent-induced BCP self-assembly kinetics (i.e., solvent evaporation rate). Next, functionalized BCP particles produced by careful design of the chemical structures of polymer or by incorporation of functional additives into the polymer matrix are introduced. Finally, this review article aims to present the challenging issues associated with current methods and future directions for research in this field.
Keywords: BLOCK-COPOLYMER NANOPARTICLES; ABC TRIBLOCK COPOLYMER; GRAPHENE QUANTUM DOTS; METHACRYLATE) COMPOSITE-PARTICLES; NONSPHERICAL COLLOIDAL PARTICLES; MICROPHASE-SEPARATED STRUCTURES; AQUEOUS DISPERSED SYSTEMS; DIBLOCK COPOLYMERS; THIN-FILMS; PHASE-SEPARATION